Dificuldades de leitura e escrita em crianças disléxicas e não-disléxicas - Hogetop, Mônica (2007)
This work has as its objective to discuss the similarities and differences between dyslexic and not dyslexic children, through the concepts and studies accomplished in the Cognitive Psychology field concerning dyslexia. The main authors studied are Salles and Parente (2006), Shaywitz(2006) and Ellis (1995) among others. The study has as its focus the reading and writing disabilities in children going through the literacy process. From the distinction between dyslexic children and the others on, it's also possible to discuss probable factors of influence for the appearance of dyslexia. Some controversies go around hypotheses, such as, the possibility of all children showing difficulties in reading and writing in the process of literacy and not only the dyslexic children, and the hypothesis of the difference between dyslexic and not dyslexic children having a quantitative or qualitative feature. There are not closed answers for this questions yet, but through the research done we can reach a higher level of knowledge, specially for acting in the education field.